Mengukur Penggunaan Sistem Informasi Akademik dalam Manajemen Akademik di IAIN Bengkulu - Safari, Edi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study is to measure the extent of the use of Academic Information System applications by student users, lecturers and management / administrators. The research method uses the theory of DeLone and McLearn Information System Success Model to measure qualitatively the use of Information Systems from the completeness of the functions / features of the application, reliability / stability, ease of use, data security, application flexibility, timeliness and management of Academic Information System applications. The results of the study, obtained information that: 1) students, lecturers and management / administrators are able to use the features / functions of the application but need to be improved socialization and education of users, 2) students, lecturers and management / administrators feel the stability / reliability of the application is good, 3) students , lecturers and management / administrators feel the ease of use of the application, 4) students, lecturers and management / administrators feel the data security is quite good but there needs to be increased data security, 5) students, lecturers and management / administrators feel the flexibility of the application is good, 6) students , lecturers and management / administrators still feel that they are not punctual in using the application due to network problems and internet access, 7) students, lecturers and management / administrators have felt quite satisfied with the management of existing applications to carry out administration and academic services. Conclusions, Academic Information Systems owned by IAIN are good enough from the dimensions of the completeness of application functions / features, application reliability / stability, ease of use, data security, application flexibility, timeliness and management of Academic Information System applications. Keywords: Academic Management, Academic Information Systems